The Role of E-S-Qual and Food Quality on Customer Satisfaction in Online Food Delivery Service - Fauziyah Sjahroeddin (Politeknik Negeri Bandung, 2018)
This study plays a role in assessing the dimensions of E-S-Qual and Food quality to improve satisfaction andperceived value in online food delivery context (OFD). Data were collected from 405 sample of customers OFDservice in Bandung and used to assess the SEM modeling. Moreover, the data, proposed model, and hypothesiswere analyses used SmartPLS 3.0 software. This study indicates that food quality is the key aspect in assessingOFD service. Although the role of food quality has the most crucial aspect, OFD service providers still have tomaintain their e-service quality in order to meet consumer expectations. Among E-S-Qual dimensions,fulfilment dimension is the most contribute to increased consumer satisfaction and perceived value in OFDservice. In short, this study suggests OFD service providers to maximise food quality and fulfill customerpromises.